Students’ Difficulties in Writing Thesis During Covid-19 Pandemic - Dewi, I Gusti Ayu Eka Susanti (Journal of Educational Study, 2022)
The COVID-19 pandemic has had a significant impact on education where regulations in schools are increasingly being tightened to prevent the spread of the virus. This causes meeting access to be limited and even full of rules that must be obeyed. This condition certainly affects the data collection process in making a thesis, especially for students who research school. This study aims to find out the difficulties faced by 7th-semester students in writing a thesis during a pandemic. The approach used is qualitative research with in-depth interview techniques in data collection. The data were then analyzed descriptively from the results of the interviews. The results showed that the difficulties faced by students were the difficulty of access and permission to enter schools during the pandemic, the passive participation of research subjects, and the unequal distribution of information. From the result, it can be concluded that those three factors are the difficulties faced by students in writing a thesis during the COVID-19 pandemic. The researcher suggests conducting research on a larger scale and wider scope to the future researcher. This research is useful in redefining policies and actions that can be taken in overcoming the factors that make it difficult for students to research so that all aspects of education can work together.